2016
DOI: 10.1021/acs.estlett.6b00074
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Mineralization in a Confined Geometry

Abstract: Injection of CO 2 in porous aquifers, where mineralization takes place via chemical reactions, is one possible long-term solution considered for storage of this greenhouse gas. This mineralization is investigated here experimentally in a confined geometry by injecting radially an aqueous solution of carbonate into a solution of calcium ions to produce solid calcium carbonate. Various precipitation patterns are observed depending on the injection rate and concentrations of the reactants. The pattern properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 13 publications
0
36
0
2
Order By: Relevance
“…This has long been known in studies on infiltration instabilities, where the invading fluid reacts with the solid matrix leading to dissolution of the solid phase and an increase in porosity (Chadam et al (1986), Daccord & Lenormand (1987), Szymczak & Ladd (2014)). More recent works have shown that precipitation locally decreasing the permeability can also induce fingering (Nagatsu et al (2014)) leading to beautiful precipitation patterns in various contexts including chemical gardens (Haudin et al (2014)) or CO2 mineralization reactions (White & Ward (2012), Schuszter et al (2014)). With no surprise, concomitant changes in viscosity and permeability can induce an interplay between viscous and precipitation-driven fingering giving rise to interesting new patterns (Nagatsu et al (2008a), Haudin & De Wit (2015)).…”
Section: Viscous Fingering In Reactive Systemsmentioning
confidence: 99%
“…This has long been known in studies on infiltration instabilities, where the invading fluid reacts with the solid matrix leading to dissolution of the solid phase and an increase in porosity (Chadam et al (1986), Daccord & Lenormand (1987), Szymczak & Ladd (2014)). More recent works have shown that precipitation locally decreasing the permeability can also induce fingering (Nagatsu et al (2014)) leading to beautiful precipitation patterns in various contexts including chemical gardens (Haudin et al (2014)) or CO2 mineralization reactions (White & Ward (2012), Schuszter et al (2014)). With no surprise, concomitant changes in viscosity and permeability can induce an interplay between viscous and precipitation-driven fingering giving rise to interesting new patterns (Nagatsu et al (2008a), Haudin & De Wit (2015)).…”
Section: Viscous Fingering In Reactive Systemsmentioning
confidence: 99%
“…Brau et al studied the dynamics of A + B → C fronts by radial injection, computing the long-time evolution of the front position, its width, and production rates of the product [27]. Their work compared well with calcium carbonate precipitation experiments [28].…”
Section: Introductionmentioning
confidence: 99%
“…14 At the macroscopic level, the presence of flows can influence the precipitation patterns obtained and produce a wide variety of complex forms. 7,12,[15][16][17][18] As an example, chemical gardens growing in 3D when placing solid metal salt seeds into alkaline solutions such as silicate are shaped by buoyancy-driven flows among other processes. 19 Control of the growth dynamics of these 3D structures has been attempted succesfully using bubble driving, 20 microgravity conditions, 21 microfluidics, 22 or the injection of one reactant into the other.…”
Section: Introductionmentioning
confidence: 99%